Fotodynamisk terapi vid behandling av skivepitelskarcinom hos katt - Nordell, Johanna (SLU/Dept. of Animal Environment and Health (until 231231), 2003)
Photodynamic therapy is a relatively new treatment for superficial squamous cell carcinoma in cats. There are no publications indicating that the method is being used in veterinary practice in Sweden at the present time. The method uses the interaction between a photosensitive agent which has been administered to the tumor area, light of a wavelength that can be absorbed by the photosensitiser and the presence of oxygen. In this study photodynamic treatments were performed at the Queen's Veterinary School Hopital of Cambridge University between 1998 and 2002. By interviewing the owner and/or the referring veterinarian in addition to reading the file copy of 25 cats which were diagnosed by histopathology with squamous cell carcinoma or squamous cell carcinoma-in-situ, a statistic analyse has been carried out to evaluate the long time outcome of the treatment, which demonstrates encouraging results. The study indicates that photodynamic therapy can be a useful method for early stage squamous cell carcinoma. A questionmark is being raised to whether a few repeated sessions of photodynamic therapy could help to decrease the common recurrence of squamous cell carcinoma that normally carries a guarded prognosis.